PENINGKATAN KREATIVITAS MELALUI KEGIATAN BELAJAR SAINS DI TK NEGERI PEMBINA KOTA SINGKAWANG - Salawati, Suchi; Ali, Muhamad; Miranda, Dian (Universitas Tanjungpura, 2024)
This study get intention to increase children's creativity by science learning assignment on 5-6 years at TK Negeri Pembina in Singkawang City. This study is action research arrange in two cycles. Subjects in this study is 5-6 year old at TK Negeri Pembina in Singkawang City with a total of 17 children. The research data is increasing children's creativity through science learning activities that are collected using observation and documentation methods with means in the form of checklists and archives or documentation. The data has been gathered was explanation with a comparativedescriptive analysis method. is it know that there is an increment in children's creativity by science learning activities on 5-6 years child at the TK Negeri Pembina Singkawang City. Because the average child at the beginning of the meeting still reaches the developing stage, and at the next meeting the child reaches the developing stage as expected. The results and conclusions of the discussion state that through science learning activities can increase inspiration children on 5-6 years in the TK Negeri Pembina Singkawang City